Assessment and spatial mapping of atmospheric corrosion amelioration using empirical equation considering environmental parameters. (3rd July 2020) - Kumar, Vanapalli Naveen; Sil, Arjun
ABSTRACT : Atmospheric corrosion is a natural surface deterioration process of the ferrous metal (steel) owing to electrochemical process with the variation of highly sensitive atmospheric parameters surrounding the metal. A global empirical model developed for estimating short-and long-term atmospheric corrosion rates by establishing empirical coefficients statistically (with R 2  = 0.99) having 95% confidence limit. It predicts atmospheric corrosion, based on the corrosion formation mechanisms and the combined impact of the environmental parameters and further abates the location and time limitations. Corrosion studies are performed for 39 years of atmospheric data collected in the study area. Environmental parameters changes in the study area over the four decades (1979–2018) are observed and corrosion map for each decade in total 39 years data based corrosion map prepared using the developed empirical equation. The developed empirical equation closely predicts atmospheric corrosion for the experimental datasets collected at 88 different continental locations while the ISO exhibits uncertainty.